Returning your call : poems - Nathan, Leonard, 1924-2007 (Princeton University Press, 1975)
Annotation 'Every poet has one or two compulsive themes, ' writes Leonard Nathan. 'One of mine is how to make things fit together that don't but should; the other is getting down far enough below a surface to see if something is still worth praising. Over the years and without self-consciously trying, I have moved closer and closer to the human voice in my verse.
Keywords: American poetry.; Poésie américaine.; POETRY -- American -- General.; FICTION -- General.; American poetry